Skin water uptake and renal function in the toad - Cirne, Bario R [UNESP]; Reis, Henrique A [UNESP]; Silveira, JoséEduardo N [UNESP] (Elsevier, 1981)
1. 1. Water balance in the toad Bufo marinus ictericus was studied by evaluating cutaneous water uptake and renal excretion. 2. 2. The permeability of the skin to water was 78 ± 6 nl min -1 cm -2 atm -1 in 60 toads anaesthetized by chloralose and preincubated in water for 3 hr. Injection of Ringer's solution did not reduce the water uptake by the skin, while hemorrhage, or injection of vasopressin, or oxytocin approximately doubled the rates of water transport. In vivo values of skin water permeability were similar to those observed in vitro. 3. 3. The renal parameters of the water balance were significantly reduced by hemorrhage and by injection of vasopressin. Injection of Ringer's solution promoted a significant increase of the urinary flow and osmolar clearance. 4. 4. It is suggested that the fight against water deprivation could proceed initially by the triggering of the urinary mechanisms of water retention, while the increase of the skin water permeability would occur in a later stage. © 1981.